1997
DOI: 10.1890/1051-0761(1997)007[0895:drcfem]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Determining Reference Conditions for Ecosystem Management of Southwestern Ponderosa Pine Forests

Abstract: The fire disturbance regime and forest structure prior to Euro‐American settlement (AD 1883) of a southwestern ponderosa pine (Pinus ponderosa) landscape were quantified in order to establish reference conditions as a baseline for ecosystem management. The mean presettlement fire interval between 1637 and 1883 was 3.7 yr for all fires and 6.5 yr for widespread fires, but fire has been excluded from the study area since 1883. Forest density increased under fire exclusion from an average of 148 trees/ha in 1883 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
258
2
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 514 publications
(270 citation statements)
references
References 30 publications
7
258
2
3
Order By: Relevance
“…Table 3 lists stand conditions, averaged by elevational grouping (low, mid, high), including trees-per-hectare (TPH), basal area (BA), and quadratic mean diameter (QMD). We compared our data with findings from Fulé et al 2007, who used tree-ring analysis to reconstruct historic conditions in northern Arizona ponderosa pine stands (2134 m elevation) [59]. That study found pre-settlement BA to range between 17 and 27 m 2 /ha (95% confidence interval), TPH to range between 51 and 79 (95% confidence interval), and QMD to range between 36 and 47 centimeters (95% confidence interval) [59].…”
Section: Baseline Conditionsmentioning
confidence: 81%
See 3 more Smart Citations
“…Table 3 lists stand conditions, averaged by elevational grouping (low, mid, high), including trees-per-hectare (TPH), basal area (BA), and quadratic mean diameter (QMD). We compared our data with findings from Fulé et al 2007, who used tree-ring analysis to reconstruct historic conditions in northern Arizona ponderosa pine stands (2134 m elevation) [59]. That study found pre-settlement BA to range between 17 and 27 m 2 /ha (95% confidence interval), TPH to range between 51 and 79 (95% confidence interval), and QMD to range between 36 and 47 centimeters (95% confidence interval) [59].…”
Section: Baseline Conditionsmentioning
confidence: 81%
“…However, we note that the silvicultural prescriptions proposed by the 4FRI team are much more complex than our design and are tailored toward multi-objective management [56,57]. A review of the literature also lent support for our management scenarios [31][32][33][59][60][61].…”
Section: Management Scenariosmentioning
confidence: 83%
See 2 more Smart Citations
“…Indeed, the appropriate range of "natural variability" is often implicitly held to be before European colonization of the North American continent (Fulé et al 1997, Moore et al 1999, Betts and Loo 2002, Oliver et al 2002. In other words, the END reflects the perspective that the "natural order" is distinct from culture-at least European culture.…”
Section: The Ethics and Values Underlying The End: A Critical Commentarymentioning
confidence: 99%